Hospital financial control strategy in the COVID-19 Pandemic era - Citra Mutiarahati, Ni Luh; Ani, Luh Seri; Suarjana, Ketut; Januraga, Pande Putu; Manuaba, I.B.G. Fajar; Lesmana, Cokorda Bagus Jaya; Indrayathi, Putu Ayu (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: The pandemic of COVID-19 is an unprecedented medical and economic challenge for healthcare system. The number of patients during pandemic of COVID-19 had a rapid growth which led to changes in services aspects that threaten financial viability of hospitals, including private hospitals. This study aims to determine the efforts of private hospitals in maintaining financial stability during the pandemic of COVID-19. Methods:  A qualitative study with a multi-case design carried out in 7 (seven) private hospitals in Denpasar. Informants were obtained based on a purposive sampling approach. This study recruited 19 informants from 7 private hospitals in Denpasar. Data was collected through in-depth interviews conducted face-to-face, using the Zoom and Whatsapp applications. The data were analysed using a content analysis approach. Results: Almost all hospitals stated that their finances disrupted. Financial mitigation efforts were difficult to do, hospital preparation and responses were dependent on the hospital's financial condition and regulations that changing, and recovery efforts were not easy either because in general the community's economy has not recovered. Conclusion: Private hospital finances were experiencing disruption. Mitigation efforts were difficult to do due to the unpredictable changing regulations and policies during the pandemic. Based on the study results, it can be recommended that the hospital management needs to develop a service strategy that is able to overcome the problem of the surge in the number of patients.